Planning nursing care in oncology: study of the structure of social representations of nurses - Rita de Cássia Velozo da SILVA; Enêde Andrade da CRUZ
Characterize the social representations of nurses regarding the planning of nursing care for people with cancer, by determining the central nucleus and of the peripheral system. Qualitative study conducted in a specialized hospital in Salvador, Bahia, between July 2008 and March 2009. Data collection was made by free association of words, with forty-one nurses. The data were processed by the software Ensemble de Programmes Permettant L'analyse des Evocationsand analyzed according to the Theory of Social Representations. The results indicated the following central elements: humanization, care, organization, individualizing and suffering. In the peripheral system, professional and personal attitudinal elements necessary for the planning were observed: skill, knowledge on the disease, family care, respect and sensitivity. It is concluded that care planning is linked to the peculiarities of the individual with cancer, and requires that nurses have knowledge and skills necessary to prioritize actions and ensure the quality of care.